A Study of Thermofluidics in Fluid Flow and Heat Transfer: Exploring Numerical Methods for Thermofluidics in Fluid Flow and Heat Transfer (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Numerous mathematical problems can be easily addressed using arithmetic operations, which iswhy they are referred to as numerical approaches. Finite element theory and other fields have been greatlyinfluenced by these approaches. Here, we've provided a brief overview of the numerical methods used inmechanical engineering to solve fluid flow and heat and mass transfer problems. These methods includesuch things as finite difference methods and finite element methods as well as those for boundary valueproblems (generally), Lattice Boltzmann methods, and those for Crank-Nicolsan scheme methods.Surface tension, coning, water dispersion, Stokes' law, gravity-capillary, and unstable free surface flows,whirling, and so on have all been explored. Additionally, we've researched boundary value andeigenvalue difficulties and established a numerical method for solving these problems. As we've shown,the performance of the mechanisms (modes) varies depending on which numerical methods are used,and these methods have been applied to several fundamental heat transfer modelling approaches.Engineering heat transfer problems can be solved using the approaches presented in this study. Wecontrasted our results with those from other methods for determining things like thermal conductivity,energy flux, entropy, and so on.